Relationship between the time from injury to surgery and the degree of fracture reduction by ligamentotaxis in a posterior instrumentation without fusion for thoracolumbar unstable burst fracture: a retrospective cohort study. Issue 2 (13th March 2021) - Ko, Sangbong; Choi, Wonkee; Lee, Jaejun; Song, Sukkyoon; Nam, Junho
Abstract : Background: This study aimed to investigate the relationship between the time from injury to surgery and the degree of fracture reduction in patients with unstable thoracolumbar burst fractures who had ligamentotaxis in a surgery in which the internal fixator was removed after obtaining union of the fractures. The surgery included posterior instrumentation with pedicle screws without an intervertebral fusion. Methods: Ninety-five patients underwent posterior instrumentation that used pedicle screws without segmental fusion as well as a removal procedure for internal fixation after obtaining union of the fracture. Those patients who were followed up for at least 1 yr after removal surgery were retrospectively enrolled. At the time of the injury, vertebral body angle was measured and the difference in the two angles was termed the correction angle. Based on the duration from injury to surgery, the patients were divided into two groups: those who had surgery within 48 hr (group A) and those who had surgery after 48 hr (group B). Results: There was a significantly weak negative correlation between the correction angle and the length of time from injury to surgery when the correlation coefficient was r=−0.205. By correcting the age, correction angle, and gender as well as increasing the correction angle by 1 degree, the probability of a subject belonging to group A was increased by 1.137 times more than the probability of a subject belonging to group B ( P =0.004). Conclusions: The time from the injury to surgery for unstable thoracolumbar burst fractures tends to be shorter with a younger age, and the shorter lead time will cause a weaker negative relationship with correction angle. Level of Evidence: Level III.